Individual Patient Data Meta-Analysis of Organ Failure in Acute Pancreatitis: Protocol of the PANCREA II Study - Das, Stephanie L M; Papachristou, George I; De Campos, Tercio; Panek, Jozefa; Poves Prim, Ignasi; Serrablo, Alejandro; Parks, Rowan W; Uomo, Generoso; Windsor, John A; Petrov, Maxim S; et al. (JOP. Journal of the Pancreas, 2013)
Context Organ failure is a major determinant of mortality in patients with acute pancreatitis. These patients usually require admission to high dependency or intensive care units and consume considerable health care resources. Given a low incidence rate of organ failure and a lack of large non-interventional studies in the field of acute pancreatitis, the characteristics of organ failure that influence outcomes of patients with acute pancreatitis remain largely unknown. Therefore, the Pancreatitis Across Nations Clinical Research and Education Alliance (PANCREA) aims to conduct a meta-analysis of individual patient data from prospective non-interventional studies to determine the influence of timing, duration, sequence, and combination of different organ failures on mortality in patients with acute pancreatitis. Methods Pancreatologists currently active with acute pancreatitis clinical research will be invited to contribute. To be eligible for inclusion patients will have to meet the criteria of acute pancreatitis, develop at least one organ failure during the first week of hospitalization, and not be enrolled into an intervention study. Raw data will then be collated and checked. Individual patient data analysis based on a logistic regression model with adjustment for confounding variables will be done. For all analyses, corresponding 95% confidence intervals and P values will be reported. Conclusion This collaborative individual patient data meta-analysis will answer important clinical questions regarding patients with acute pancreatitis that develop organ failure. Information derived from this study will be used to optimize routine clinical management and improve care strategies. It can also help validate outcome definitions, allow comparability of results and form a more accurate basis for patient allocation in further clinical studies. Image: Acute pancreatitis and organ failure.